High-Impact Minimum Wages and Heterogeneous Regions - Philipp Vom Berge; Hanna Frings (Institute of Labor Economics (IZA), 2017)
We estimate the effects of the introduction and subsequent increases of a substantial minimum wage in Germany's main construction industry on wage and employment growth rates. Using a regional dataset constructed from individual employment histories, we exploit the spatial dimension and border discontinuities of the regional data to account for spillovers between districts and unobserved heterogeneity at the local level. The results indicate that the minimum wage increased the wage growth rate for East Germany but did not have a significant impact on the West German equivalent. The estimated effect on the employment growth rate reveals a contraction in the East of about 1.2 percentage points for a one-standard-deviation increase in the minimum-wage bite, amounting to roughly one quarter of the overall decline in the growth rate. We observe no change for the West.
Keywords: J31; J38; 330; construction sector; Germany; minimum wage; spatial heterogeneity; spatial panel data